Induction Shoots of Black Pomegranate (Punica granatum L.) Seed Explant Using Thidiazuron And Kinetin Hormone In Vitro - Popilia, Intan; Linalatil F, Khanna; Rohmah, Mita Devi (El-Hayah : Jurnal Biologi, 2021)
Pomegranate is a fruit that has medicinal properties, it is proven by antibacterial, anti-inflammatory and anticancer activity. The aim of this study was to determine the best concentration of cytokinins in inducing shoots of black pomegranate seed explants (Punica granatum L.) in vitro. This study used one factorial, namely the addition of various concentrations of TDZ and kinetin. TDZ factor and kinetin with 6 treatment levels, namely 0 mg / L, 0.1 mg / L, 0.2 mg / L, 0.3 mg / L, 0.4 mg / L, and 0.5 mg / L, each treatment was repeated 4 times, for a total of 24 experimental units. The parameters observed included the day when the shoots appeared, the number of leaves, the length of the shoots and the day the leaves were fully open. Observation data were analyzed using Kruskal Wallis. The data showed that the cytokinin hormone, both kinetin and TDZ, was not able to significantly induce shoots on black pomegranate seed explants (Punica granatum L.). The hormone kinetin was able to induce shoots on explants of black pomegranate seeds (Punica granatum L.) with the best concentration of 0.4 ppm but the results were not significant. The optimal TDZ concentration in inducing callus appearance was 0.4 ppm with a callus appearance time of 24 DAP.